Behavioral Economics: Understanding the Psychological Factors Driving Consumer Decisions - Chen, Qi (International Journal of Global Economics and Management, 2024)
Behavioral economics is an interdisciplinary field that combines insights from psychology and economics to explain and predict consumer behavior in economic decision-making. This article provides a concise overview of the definition and importance of behavioral economics, exploring its core concepts such as bounded rationality, heuristics and biases, and prospect theory. It also examines the impact of emotional and social factors on consumer decisions and discusses practical applications of behavioral economics in marketing and public policy. Finally, the article summarizes key points and looks ahead to future directions in the field.